2014
DOI: 10.1021/ja507119n
|View full text |Cite
|
Sign up to set email alerts
|

Superacidity in Sulfated Metal–Organic Framework-808

Abstract: Superacids, defined as acids with a Hammett acidity function H0 ≤ -12, are useful materials, but a need exists for new, designable solid state systems. Here, we report superacidity in a sulfated metal-organic framework (MOF) obtained by treating the microcrystalline form of MOF-808 [MOF-808-P: Zr6O5(OH)3(BTC)2(HCOO)5(H2O)2, BTC = 1,3,5-benzenetricarboxylate] with aqueous sulfuric acid to generate its sulfated analogue, MOF-808-2.5SO4 [Zr6O5(OH)3(BTC)2(SO4)2.5(H2O)2.5]. This material has a Hammett acidity funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

28
491
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 497 publications
(535 citation statements)
references
References 67 publications
(24 reference statements)
28
491
5
Order By: Relevance
“…Zr-based MOF-808-P was synthesized according to the reported procedure, starting from ZrOCl 2¨8 H 2 O and 1,3,5-benzenetricarboxylic acid (BTC) dissolved in a mixture of N,N-dimethylformamide (DMF) and formic acid [32]. In contrast to the MOF-808 synthesis employing stoichiometric amounts of linker (ZrOCl 2 /BTC = 1/1) [31], MOF-808-P is synthesized with an excess of Zr-source (ZrOCl 2 /BTC = 3/1), resulting in formic acid ligand deficiency and an increased number of Lewis acid sites at the under-coordinated Zr-metal.…”
Section: Reduction Of Cinnamaldehyde and Carvonementioning
confidence: 99%
See 1 more Smart Citation
“…Zr-based MOF-808-P was synthesized according to the reported procedure, starting from ZrOCl 2¨8 H 2 O and 1,3,5-benzenetricarboxylic acid (BTC) dissolved in a mixture of N,N-dimethylformamide (DMF) and formic acid [32]. In contrast to the MOF-808 synthesis employing stoichiometric amounts of linker (ZrOCl 2 /BTC = 1/1) [31], MOF-808-P is synthesized with an excess of Zr-source (ZrOCl 2 /BTC = 3/1), resulting in formic acid ligand deficiency and an increased number of Lewis acid sites at the under-coordinated Zr-metal.…”
Section: Reduction Of Cinnamaldehyde and Carvonementioning
confidence: 99%
“…It has often been observed that traces of DMF can be strongly adsorbed in the MOF structure, especially for MOF-808-P, since the missing formate ligand is most likely replaced by a DMF or water molecule [32]. ICP-AES indicates a Zr weight percentage of 39.4 +/´0.7 wt %, a little lower than the theoretical 40 wt % when all missing linkers would be replaced by water.…”
Section: Reduction Of Cinnamaldehyde and Carvonementioning
confidence: 99%
“…[13]. Metal-organic framework MOF-808 was constructed by linking Zr 6 O 4 (OH) 4 (−CO 2 ) 6 (HCOO) 6 as secondary building unit (SBU) with six BTC units to form 3-D porous framework [14][15]. However, MOF-808 nanocrystals were synthesized using solvothermal method under high temperatures (150 o C) and long reaction times (3-7 days) [14][15].…”
Section: Introductionmentioning
confidence: 99%
“…In order to prepare the samples for gas sorption analysis, a gentle process involving solvent exchange and activation at room temperature was performed following a previously reported procedure. 27 The included water in 1 was exchanged three times each for methanol and then chloroform, after which the sample was rapidly filtered, transferred into the sample tube for gas sorption analysis and placed under vacuum for activation at room temperature. Activation was continued for 1 -2 weeks, after which the N 2 gas sorption analysis was performed.…”
mentioning
confidence: 99%
“…Sulfoacetic acid and sulfuric acid were chosen because it has previously been demonstrated that sulfuric acid can bind to related zirconium clusters and strongly increase the acidity of the MOF. 27 All of the treated samples were washed extensively and soaked multiple times in ultrapure water to ensure the removal of any residual acid. The carboxylic acid additives were added during synthesis with the hope that they may also fill some of the defective zirconium cluster sites and increase the stability of the and a second residual peak (s 3.17 ppm), giving a 25:1 ligand to sulfoacetate ratio; the second residual peak may be a result of the partial decomposition of the sulfoacetic acid during synthesis or NMR sample preparation.…”
mentioning
confidence: 99%